Observation of Spectral Structures in the Flux of Cosmic-Ray Protons from 50 GeV to 60 TeV with the Calorimetric Electron Telescope on the International Space Station - Adriani, O.; Akaike, Y.; Asano, K.; Asaoka, Y.; Cannady, Nicholas; Hams, Thomas; Sakai, Kenichi; et al (APS, 2022)
A precise measurement of the cosmic-ray proton spectrum with the Calorimetric Electron Telescope (CALET) is presented in the energy interval from 50 GeV to 60 TeV, and the observation of a softening of the spectrum above 10 TeV is reported. The analysis is based on the data collected during ∼6.2 years of smooth operations aboard the International Space Station and covers a broader energy range with respect to the previous proton flux measurement by CALET, with an increase of the available statistics by a factor of ∼2.2. Above a few hundred GeV we confirm our previous observation of a progressive spectral hardening with a higher significance (more than 20 sigma). In the multi-TeV region we observe a second spectral feature with a softening around 10 TeV and a spectral index change from −2.6 to −2.9 consistently, within the errors, with the shape of the spectrum reported by DAMPE. We apply a simultaneous fit of the proton differential spectrum which well reproduces the gradual change of the spectral index encompassing the lower energy power-law regime and the two spectral features observed at higher energies.
Authors: O. Adriani, Y. Akaike, K. Asano, Y. Asaoka, E. Berti, G. Bigongiari, W. R. Binns, M. Bongi, P. Brogi, A. Bruno, J. H. Buckley, N. Cannady, G. Castellini, C. Checchia, M. L. Cherry, G. Collazuol, K. Ebisawa, A. W. Ficklin, H. Fuke, S. Gonzi, T. G. Guzik, T. Hams, K. Hibino, M. Ichimura, K. Ioka, W. Ishizaki, M. H. Israel, K. Kasahara, J. Kataoka, R. Kataoka, Y. Katayose, C. Kato, N. Kawanaka, Y. Kawakubo, K. Kobayashi, K. Kohri, H. S. Krawczynski, J. F. Krizmanic, P. Maestro, P. S. Marrocchesi,† A. M. Messineo, J. W. Mitchell, S. Miyake, A. A. Moiseev, M. Mori, N. Mori, H. M. Motz, K. Munakata, S. Nakahira, J. Nishimura, G. A. de Nolfo, S. Okuno, J. F. Ormes, S. Ozawa, L. Pacini, P. Papini, B. F. Rauch, S. B. Ricciarini, K. Sakai, T. Sakamoto, M. Sasaki, Y. Shimizu, A. Shiomi, P. Spillantini, F. Stolzi, S. Sugita, A. Sulaj, M. Takita, T. Tamura, T. Terasawa, S. Torii, Y. Tsunesada, Y. Uchihori, E. Vannuccini, J. P. Wefel, K. Yamaoka, S. Yanagita, A. Yoshida, K. Yoshida, and W. V. Zober